The validity and reliability of a Turkish version of the Poverty-Related Quality of Life (PQoL) questionnaire. Issue 4 (1st October 2016) - Yilmaz, Fikriye
Abstract: Measuring poverty in health care settings may help to identify patients living in poverty and also support development of appropriate policies to reduce health inequalities. The objective of this study was to translate the Poverty-Related Quality of Life Questionnaire into Turkish and then test its validity and reliability for a Turkish patient population. The psychometric properties of the scale were examined by collecting data from 300 patients in emergency departments in three randomly selected hospitals in Ankara, Turkey. The results of the study suggest that the Turkish version of the Poverty-Related Quality of Life Questionnaire has satisfactory validity and reliability.